The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0022034516659041
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Regulates Homeostasis of Mesenchymal Stem Cells and Regulatory T Cells

Abstract: Hydrogen sulfide (H 2 S) has long been known as a toxic gas. However, recently accumulated evidence suggests that H 2 S contributes to a variety of physiologic and pathologic processes. Endogenous H 2 S production is regulated by multiple enzymes that are differentially expressed in the cardiovascular, neuronal, immune, renal, respiratory, gastrointestinal, reproductive, liver, and endocrine systems. Alteration of H 2 S metabolism may affect multiple signaling pathways and tissue homeostasis. The growing numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…H 2 S is a gaseous transmitter that has recently been associated with the function of MSCs and bone metabolism [ 25 ]. It has been elucidated that the production of force-induced H 2 S in hPDLSCs modulated the accumulation of macrophage and osteoclastic and osteogenic activities in the alveolar bone through regulation of the secretion of monocyte chemoattractant protein-1 and the receptor activator of the nuclear factor- κ B ligand/osteoprotegerin (RANKL/OPG) system and then controlled the process of OTM [ 26 ].…”
Section: The Molecules Transmitting the Orthodontic Force To Pdlscmentioning
confidence: 99%
“…H 2 S is a gaseous transmitter that has recently been associated with the function of MSCs and bone metabolism [ 25 ]. It has been elucidated that the production of force-induced H 2 S in hPDLSCs modulated the accumulation of macrophage and osteoclastic and osteogenic activities in the alveolar bone through regulation of the secretion of monocyte chemoattractant protein-1 and the receptor activator of the nuclear factor- κ B ligand/osteoprotegerin (RANKL/OPG) system and then controlled the process of OTM [ 26 ].…”
Section: The Molecules Transmitting the Orthodontic Force To Pdlscmentioning
confidence: 99%
“…A relevant increase in brain tissue CBS relative expression was obtained in accordance with [74,[82][83] Where MSCs are vital progenitor cells owing the capability to differentiate into vital cells with maintaining tissue homeostasis and proliferation of neural stem cells. While a suppression in oxidative stress brain tissue level (MDA) with a simultaneous increase in (GSH) was observed following intracerebral MSCs transplantation.These obtained results are in accordance with [12], where oxidative stress markers in brain tissue were suggested to be suppressed by intracerebral transplantation of MSCs as a result of expressing antiinflammatory cytokines involved in brain tissue repair introduced by MSCs via Bcl2 activation with attenuating Bax expression preventing brain damage [12,84].An additional beneficial action of transplanting MSCs intracerebrally within LPS induced AD in rats was their ability to suppress ACAT brain tissue relative expression level, which can not only be related to the lipid engulfing macrophage polarization effect but also to its ability to suppress inflammatory cascades such as TNF-α expression and caspase-3 where they play a vital role in up regulating the brain cholesterol ACAT level [12,[85][86].…”
Section: Discussionmentioning
confidence: 54%
“…Again, it is noteworthy another aspect regarding the importance of CSE/H 2 S system in the bone context, namely in bone tissue engineering. It has in fact been recently demonstrated that cells exposed to H 2 S have potential applications in regenerative medicine, since modulation of H 2 S metabolism may serve as a therapeutic approach to promote the viability of transplanted mesenchymal stem cells (MSCs) and facilitate MSC-based regeneration [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%